Patient awareness and perception regarding anesthesia and the role of anesthesiologists: A cross-sectional study in a tertiary care hospital - Hirachan, Rozeeta; Bhattarai, Kushal Mohan; Pahari, Thaneshwor; Neupane, Sandeep; Shrestha, Anu (Journal of Gandaki Medical College-Nepal, 2026)
Background: There have been significant advancements in the scope of anesthesia, however, it has been misconceived as a behind the screen specialty. Patients are not aware of anesthesiologist as a qualified health professional, especially in under-developed countries. This knowledge gap may adversely affect informed consent and perioperative anxiety management. Hence, this study aimed to assess patient`s knowledge and perception regarding anesthesia, evaluate concerns about surgical interventions and determine associations between educational level and previous anesthetic exposure with awareness about anesthesia types. Methods: An institutional based cross- sectional study was conducted from November 2025 to January 2026 in patients aged 18 to 75 years. Around 370 patients were interviewed with a structured questionnaires with 12 items to assess patients’ knowledge, perception and concerns of anesthesia. Descriptive statistics and Chi-square tests were used for analysis. Results: Out of 370 patients, only 80(21.60%) correctly identified anesthesiologists as the health care professionals responsible for administering anesthesia. Most patients 283(76%) lacked knowledge about anesthetic types. A statistically significant association was found between education level and awareness of anesthetic types (p<0.001) and between previous anesthetic exposure and awareness of anesthetic types (p<0.0001). Conclusions: Patient awareness regarding anesthesia and the peri-operative role of anesthesiologists was limited. Higher educational attainment and previous anesthetic exposure were associated with improved awareness.